Assessment of regional Ecosystem Service Bundles coupling climate and land use changes - Hao Su; Mingxi Du; Qiuyu Liu; Xiang Kang; Li Zhao; Wei Zheng; Ziyan Liao (Ecological Indicators)
Escalating land use and cover change (LUCC) trends and intensifying impacts of climate change have brought about a global decline in ecosystem services (ESs). Historical and current ES Bundles (ESBs) are usually investigated as representative of ES capacities. However, whether the coupling impact of future climate and LUCCs on regional ESBs will be facilitated or inhibited is still unclear. Here, we evaluate and simulate the ESBs of Shaanxi Province, a typical region of Northwest China, from 2000 to 2050. We find that future land use patterns are characterized by the incremental amount of ecological land area and construction land, while arable land faces a significant decline. Moreover, we observe trade-offs in water-related ES pairs due to precipitation latitudinal zonation and topography, while other ESs exhibit synergistic relationships. As climate and land use changes intensify, the transformation probability among ecological and barren ESBs becomes progressively stronger. We recommend focusing on ES interactions and the comprehensive rehabilitation of regional ESs to improve the ESBs of ecologically fragile and urbanized areas.